High Resolution Distributed Optical Fiber Sensing Using Time-Expanded Phase-Sensitive Reflectometry - Fernández-Ruiz, María R.; Soriano-Amat, Miguel; Martins, Hugo F.; Durán, Vicente; Martin-Lopez, Sonia; Gonzalez-Herraez, Miguel (Frontiers in Sensors, 2022)
We have demonstrated a novel scheme for distributed optical fiber sensing based on the use of a dual frequency comb, which enables the development of a high-resolution (in the cm range) distributed sensor with significantly relaxed electronic requirements compared with previous schemes. This approach offers a promising solution for real time structure monitoring in a variety of fields, including transportation, manufacturing or mechatronics. In this work, we review the principle of operation of the technique, recent advances to improve its performance and different experimental tests.